Balancing Harvest and Habitat: A Framework for the Sustainable Management of Diadromous Galaxiids - Ben R. J. Crichton; Michael J. H. Hickford; Angus R. McIntosh; David R. Schiel; Andrew S. Watson (New Zealand Journal of Marine and Freshwater Research, 2026)
Managing New Zealand's diadromous Galaxias species and the associated whitebait fishery presents a complex challenge due to species‐specific differences in life‐history strategies, habitat requirements, and population dynamics that underpin responses to anthropogenic and environmental pressures. Consequently, effective management must balance the distinct vulnerabilities and dependencies of each species to ensure long‐term sustainability. This complexity is evident in the fishery's differential impacts, where fishing primarily affects early life stages in kōkopu species but has broader consequences for īnanga populations. The long lifespan of kōkopu species buffers them against short‐term recruitment variation, whereas the annual life cycle of īnanga results in availability of recruits having a direct effect on adult population size. Although fishing closures support larval escapement, the overall benefit to galaxiid populations depends heavily on the quality of habitats that support post‐larval development and adult spawning. An effective management strategy should, therefore, combine targeted fishing regulations with the protection and restoration of high‐quality habitats at regional and national scales to allow sustainable recreational and cultural harvests. This dual approach is critical for sustaining īnanga populations by ensuring sufficient recruits reach adulthood, while also supporting kōkopu by maximising adult carrying capacities and overall population productivity.